Cobalt(III) complexes with thiosemicarbazones as potential anti-Mycobacterium tuberculosis agents - Oliveira, Carolina G.; Maia, Pedro Ivo Da S.; Miyata, Marcelo [UNESP]; Pavan, Fernando Rogério [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Almeida, Eduardo Tonon De; Deflon, Victor M. (Sociedade Brasileira de Química, 2014)
CoIII complexes derived from 2-acetylpyridine N(4)-R thiosemicarbazone (Hatc-R, R = alkyl, aryl) have been characterized by elemental analysis, FTIR, UV-Visible and 1H NMR spectroscopies, cyclic voltammetry (CV), conductimetry measurements and single crystal X-ray diffractometry. The results obtained are consistent with the oxidation of the CoII center to CoIII upon coordination of the monoanionic N,N,S-tridentate thiosemicarbazone ligands, resulting in octahedral ionic complexes of the type [Co(atc-R)2]Cl. Electrochemistry studies show two reversible processes referring to the redox couples CoIII/CoII and CoII/CoI which can be modified by the inductive effects of the substituents groups at the N4 position of the ligands. Two CoIII complexes showed satisfactory activity with minimal inhibitory concentration value under 10 µmol L - 1 and one presented quite low cytotoxicity against VERO and J774A.1 cells (IC50), resulting in high selectivity index (SI > 10).

Complexos de CoIII derivados da 2-acetilpiridina N(4)-R tiossemicarbazona (Hatc-R, R = alquil ou aril) foram caracterizados por análise elementar, espectroscopia na região do infravermelho, UV-Visível e 1H RMN, voltametria cíclica (VC), medidas de condutividade e difração de raios X em monocristal. Os resultados obtidos são consistentes com a oxidação do centro de CoII para CoIII após a coordenação N,N,S-tridentada e monoaniônica dos ligantes tiossemicarbazonas, resultando em complexos octaédricos iônicos do tipo [Co(atc-R)2]Cl. Os estudos de eletroquímica mostram dois processos reversíveis, referentes aos pares redox CoIII/CoII e CoII/CoI, que são afetados pelo efeito indutivo dos grupos substituintes na posição N4 dos ligantes. Dois complexos de CoIII se mostraram satisfatoriamente ativos, com valores de concentração inibitória mínima abaixo de 10 µmol L - 1 e um deles apresentou muito baixa citotoxicidade contra células VERO e J774A.1 (IC50), conferindo-lhe altos índices de seletividade (SI > 10).
Keywords: cobalt(III); thiosemicarbazones; anti-mycobacterium tuberculosis activity